Incidence and predictors of mortality among adult trauma patients admitted to the intensive care units of comprehensive specialized hospitals in Northwest Ethiopia - Mengistu Abebe Messelu; Ambaye Dejen Tilahun; Zerko Wako Beko; Hussien Endris; Asnake Gashaw Belayneh; Getayeneh Antehunegn Tesema (European Journal of Medical Research, 2023)
Abstract Background Trauma is the leading cause of morbidity and mortality among adult population in the world. Despite many improvements in technology and care, mortality among trauma patients in the intensive care unit is still high particularly in Ethiopia. However, there is limited evidence on the incidence and predictors of mortality among trauma patients in Ethiopia. Therefore, this study aimed to assess the incidence and predictors of mortality among adult trauma patients admitted to intensive care units. Methods Institutional-based retrospective follow-up study was conducted from January 9, 2019 to January 8, 2022. A total of 421 samples were chosen using simple random sampling. Data were collected with Kobo toolbox software and exported to STATA version 14.1 software for data analysis. Kaplan–Meier failure curve and log-rank test were fitted to explore the survival difference among groups. After the bivariable and multivariable Cox regression analysis, an Adjusted Hazard Ratio (AHR) with 95% Confidence Intervals (CI) was reported to declare the strength of association and statistical significance, respectively. Result The overall incidence rate of mortality was 5.47 per 100 person-day observation with a median survival time of 14 days. Did not get pre-hospital care (AHR = 2.00, 95%CI 1.13, 3.53), Glasgow Coma Scale (GCS) score < 9 (AHR = 3.89, 95%CI 1.67, 9.06), presence of complications (AHR = 3.71, 95%CI 1.29, 10.64), hypothermia at admission (AHR = 2.11, 95%CI 1.13, 3.93) and hypotension at admission (AHR = 1.93, 95%CI 1.01, 3.66) were found significant predictors of mortality among trauma patients. Conclusion The incidence rate of mortality among trauma patients in the ICU was high. Did not get pre-hospital care, GCS < 9, presence of complications, hypothermia, and hypotension at admission were significant predictors of mortality. Therefore, healthcare providers should give special attention to trauma patients with low GCS scores, complications, hypotension, and hypothermia and better to strengthen pre-hospital services to reduce the incidence of mortality.